Determination of Superoxide Radical Scavenging Activity and Total Antioxidant Capacity by Modified DMPD Method - Ferda Dondurmacıoğlu (Journal of Advanced Research in Natural and Applied Sciences)
Among the reactive oxygen species, Superoxide radicals can produce dangerous species that cause lipid peroxidation. Therefore, the determination and scavenging of superoxide radicals is critical. Our study is based on the interaction of the superoxide radical produced from the β-Nicotinamide adenine dinucleotide reduced disodium salt hydrate and phenazine methosulfate (NADH-PMS) system with N, N-dimethyl-p-phenylenediamine dihydrochloride (DMPD) to form the pink colored DMPD-quinone (DMPDQ) radical. In the presence of scavengers with superoxide radical scavenging activity (antioxidants, herbal teas) the color intensity decreases due to reduced DMPDQ radical production. The absorbance of the colored reference solution and the sample solution containing the radical scavenger was measured at 552 nm. The difference in absorbance (ΔA) between the reference solution and the sample solution was found. ΔA is proportional to the scavenger concentration. In the study, the superoxide radical scavenging effect of trolox (TR) and different AOXs was investigated. The superoxide radical scavenging effect of three different herbal tea infusion solutions was measured with this method. From the graph drawn between herbal tea concentrations and percentage inhibition values, 50% inhibition (EC50) values of herbal teas were found. EC50 method values were compared with the EC50 values of the nitroblue tetrazolium (NBT) and the 2,2'-azino-bis(3-etilbenzotiyazolin-6-sülfonik asit (ABTS) method. In addition, ABTS, cupric reducing antioxidant capacity (CUPRAC), and this study total antioxidant capacity (TAC) values of herbal tea infusions were calculated and compared.